2005
DOI: 10.12968/bjon.2005.14.14.18549
|View full text |Cite
|
Sign up to set email alerts
|

Improving service delivery for relapse management in multiple sclerosis

Abstract: This action research study was conducted over an 18 month period within a district general hospital. The study has improved the quality of the service provided to people experiencing a relapse of multiple sclerosis. The authors now identify and treat a three-fold increase in relapse patients. At least 85% of these patients are treated within 10 days of reporting symptoms to a specialist nurse. Before the study, only 12% of patients received treatment within this time. The authors' data identify what patients v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several studies failed to adequately describe comparison groups (Crocker 2002, Currie et al. 2004, Ayers 2005, Warner et al. 2005, Kirk 2007, Mason 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies failed to adequately describe comparison groups (Crocker 2002, Currie et al. 2004, Ayers 2005, Warner et al. 2005, Kirk 2007, Mason 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in symptomatic outcomes were evident in several quantitative and survey studies, including both physical (Pottle 2005, James & McPhail 2008, Mason 2009) and psychological outcomes (e.g. Warner et al. 2005), such as reduced anxiety (Marshall et al.…”
Section: Resultsmentioning
confidence: 99%
“…Restraint use was conditioned not only by clinical factors but mainly by organizational factors related to staff, structure and health guidelines which, over an 8-year period, allowed its significant reduction. Only a multidimensional approach [ 72 - 74 ] could face out almost completely this procedure since violence is a complex and multi-faceted phenomenon [ 75 ]. Other studies aimed to explore the relationship between patients and staff are necessary to better identify innovative strategies for reducing violence in health settings [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis nurses facilitate a timely response to relapses; in one study 69 patients reported their relapse symptoms to a nurse sooner (within 10 days of onset) compared with a mean time of 51 days when reporting the same symptoms to a general practitioner; 85% of patients were treated for their relapse within 10 days of first reporting symptoms; and a threefold increase in treatment capacity occurred. In a more recent study, a noticeable reduction in hospital bed utilisation by patients with multiple sclerosis was seen.…”
Section: The Role Of the Multiple Sclerosis Specialist Nursementioning
confidence: 99%